Probable case of Cephalotheca foveolata bloodstream infection. Issue 4 (August 2015) - Lu, Lenette L.; Weil, Ana A.; Wiederhold, Nathan; Sutton, Deanna A.; Chesnut, Lauren; Lindner, Jonathan; Fan, Hongxin; Tingpej, Bhatraphol; El-Khoury, Joseph; Kwon, Douglas S.
Abstract : Introduction: Cephalotheca foveolata is a saprobic fungus recently described among clinical isolates. Case presentation: A 59-year-old man presented with fevers, upper back pain and shortness of breath after gastric tube removal following an oesophagectomy, oesophagojejunostomy and gastrostomy for management of oesophogeal adenocarcinoma. He had a suspected oesophageal leak and polymicrobial empyema. Blood cultures grew only C. foveolata. He improved clinically on empiric antifungal and broad-spectrum antibacterial therapy. Conclusion: We report a probable case of C. foveolata bloodstream infection. This is a newly recognized pathogen requiring molecular diagnostic methods to make an accurate diagnosis.